2022
DOI: 10.1136/bmjgh-2022-009594
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on access to and utilisation of services for sexual and reproductive health: a scoping review

Abstract: IntroductionThe COVID-19 pandemic has negatively impacted health systems globally and widened preexisting disparities. We conducted a scoping review on the impact of the COVID-19 pandemic on women and girls’ access to and utilisation of sexual and reproductive health (SRH) services for contraception, abortion, gender-based and intimate partner violence (GBV/IPV) and sexually transmitted infections (STIs).MethodsWe systematically searched peer reviewed literature and quantitative reports, published between Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 117 publications
(619 reference statements)
3
30
1
1
Order By: Relevance
“…Some scoping reviews are currently investigating the impact of COVID-19, with specific focus on access to and utilization of services for sexual and reproductive health. This includes services for gender-based violence and IPV [ 21 ], while others are looking at virtual supports and IPV services [ 22 ]. There are also reviews underway on women’s mental health and experience of IPV following natural disasters [ 23 ] and the impact of IPV on work and employment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some scoping reviews are currently investigating the impact of COVID-19, with specific focus on access to and utilization of services for sexual and reproductive health. This includes services for gender-based violence and IPV [ 21 ], while others are looking at virtual supports and IPV services [ 22 ]. There are also reviews underway on women’s mental health and experience of IPV following natural disasters [ 23 ] and the impact of IPV on work and employment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…STI care was especially affected early in the pandemic, when many outpatient clinics closed, stay-at-home orders were put in place, and there was widespread fear of accessing medical facilities. This may have led to delays in seeking care, difficulty accessing lab testing or medical treatment for STIs ( 1 ), or preferential utilization of the emergency department (ED) for STI care, as EDs remained open for in-person care throughout the pandemic. Even before the COVID-19 pandemic, the ED was already the preferred location of care for many vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
“…A few quantitative studies exist with this aim [12][13][14][15][16], one of which found 20% of surveyed community members in Burkina Faso, Ethiopia, and Nigeria reported difficulty in accessing family planning services due to COVID-19 [13]. To our knowledge, limited studies have qualitatively explored the possible effects of COVID-19 on family planning service delivery and access to-date [17]. In addition, researchers posit that other known determinants of family planning related to gender inequity may be exacerbated by COVID-19 [18], which may be particularly relevant in settings such as Uganda.…”
Section: Introductionmentioning
confidence: 99%